Hepatic Angiosarcoma May Have Fair Survival Nowadays. Issue 19 (May 2015) - Huang, Neng-Chyan; Kuo, Yau-Chang; Chiang, Jui-Chin; Hung, Shih-Yuan; Wang, Huay-Min; Hung, Yao-Min; Chang, Yun-Te; Wann, Shue-Ren; Chang, Hong-Tai; Wang, Jyh-Seng; Ho, Sheng-Yow; Guo, How-Ran; et al.
<x xml:space="preserve">Abstract</x> Abstract Hepatic angiosarcoma (HAS) is rare but often fatal. A review of literature in 1979 found that only 3% of the 70 patients lived for more than 2 years, but the survival might have been improved over the years. We conducted a retrospective study and reviewed the medical records of patients who visited a teaching hospital in Taiwan from January 2000 to August 2010 and had pathological proof of HAS. In addition, we conducted a review of literature and compared those who survived for 2 years or more to those who did not. Of the 3503 patients with primary liver cancer we identified, 9 had HAS, of whom 3 (33.3%) survived for 2 years or more. One survived for 24 months without surgical resection, and the other two received surgery with postoperative chemotherapy and were still alive 32 and 37 months later, respectively. Through reviewing literature, we identified 3 more patients in Taiwan who had survived for 2 years or more. One survived for 42 months without surgical resection, the other two received segmentectomy with postoperative chemotherapy or radiotherapy. We also identified 8 such cases outside Taiwan, including 1 who received chemotherapy without surgery and survived for 53 months. None of the differences in the clinical characteristics between those who had and had not survived for 2 years or more reached statistical significance. In conclusion, we believe the combination of surgery and adjuvant chemotherapy may be able to achieve long-term survival in some HAS patients nowadays, and it is even possible to achieve fair survival using chemotherapy alone.